Levels of metals (Al, Cr, V, As, Se) in PM10 particles in the atmosphere of the town of Barrancas, North Colombia. - Argumedo, Carlos Doria (AiBi Journal of Research, Administration and Engineering, 2020)
Taking into account the different studies on the levels of contamination generated by the particles that mention the dangers to human health associated with the increased inhalation of the mass of PM10 particles and their metallic composition, the levels of: Al , Cr, V, As, Se; generated by the re-suspension of the soil, as a natural source; and coal mining activities and vehicular traffic, such as the most important anthropogenic sources, in the town of Barrancas, La Guajira, Colombia. The monitoring program contemplated the definition of three strategically located sites, taking into account the mining activities of coal extraction, as well as agriculture and livestock; During the dry and rainy seasons. Quartz filters were used to collect the PM10 particles, by means of Hi-Vol high volume samplers, in a period of 10 months for a total of 30 samples. The filters were subjected to an acid digestion process to extract the metals, which were analyzed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The concentration of PM10 particles exceeded the annual standard of 20 μg / m3 established by the WHO. The PM10 particles are mainly made up of Al (1.17 μg / m3 + 0.14) and Fe (0.53 μg / m3 + 0.30). The statistical analysis allowed determining that, between the sampling sites, there were no significant differences. V levels do not exceed the air quality standard established for Colombia; but As levels slightly exceed the WHO allowable limit. Additionally, the statistical analysis allowed concluding that in the area there is only one source of origin, natural or anthropogenic, responsible for the presence of metals in the particulate material.